If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-k+8=-3(k-4)
We move all terms to the left:
-k+8-(-3(k-4))=0
We add all the numbers together, and all the variables
-1k-(-3(k-4))+8=0
We calculate terms in parentheses: -(-3(k-4)), so:We get rid of parentheses
-3(k-4)
We multiply parentheses
-3k+12
Back to the equation:
-(-3k+12)
-1k+3k-12+8=0
We add all the numbers together, and all the variables
2k-4=0
We move all terms containing k to the left, all other terms to the right
2k=4
k=4/2
k=2
| 8x=-−128 | | 8x-84=3x+36 | | 8x-3=+10x | | -8=-2+-2r | | 17-4x=13-3x | | 6c+20-c=3c+2+5c | | 2x-4/6=2x+2/12 | | 3+2x/5=5x/10-10 | | -3-2(7k+6)=-113 | | -3/4x+3=21 | | 2/5x10=30 | | 2c-4=4c | | m/4-7=-4 | | -0.5k-3.69=k-1.9-2.39 | | 4(2x-3)+2=3x | | 0.25x^2+2x-45=0 | | 8b+6+3=9+8b | | 3x+15=2(4x-5) | | F(n)=7n-24 | | 3n-5=n=7 | | 2.5x+6.4=3.6 | | 3/2(n+7)=5/2-n | | 8x=−128 | | 15y+27=102 | | (6x+27)=(12x+9) | | 9/5x+12=21 | | 7x+3(x-2)=14 | | 3(2m)+3)=-15 | | -5y=4y | | 3x+3=-2x+-7 | | n9=-10 | | -5y=46 |